The Negative Effect of Time Budget Pressure to Auditor Independence and Professional Skepticism - Andi Ina Yustina; Stephanie Angelica Gonadi (Institute of Research and Community Outreach - Petra Christian University, 2019)
This research examines whether time budget pressure affect professional scepticism and if so, whether the affect is mediated by auditor independency. A web-based survey is used in deploying and delivering questionnaires to 163 auditors from big four and non-big four in Jakarta. The result shows that auditor independency (AI) is partially mediated the relationship between time budget pressure (TBP) and professional scepticism (PS). Which means, external auditor in Jakarta who experiencing high time pressure will tend to decrease their independency and resulted a low scepticism. Seeing this result, this study suggests by increasing number of audit team member, set the number of minimum supporting evidence and having supervisor to monitor auditor’s job, will help to minimize the negative effect of time pressure.